Paratanaoidean tanaidaceans (Crustacea: Peracarida) from littoral and shallow sublittoral habitats in New Zealand, with descriptions of three new genera and seven new species - Bird, G.J. (Zootaxa, 2011)
Three new genera and seven new species of paratanaoidean tanaidaceans are described from a variety of littoral and shallow sublittoral habitats around New Zealand, from the Snares Islands to Northland. These include a new leptocheliid genus, Parakonarus , closely allied to Konarus Bamber, and three paratanaids: two species of Paratanais Dana and a new genus, Atemtanais , which appears to show char acters intermediate between Metatanais Shiino and Paratanais . The remaining three taxa belong either to the Tanaellidae (a new species of Araphura Bird & Holdich) or are of incertae sedis family status: Kanikipa n. gen. and a new species of Tanaopsis G. O . S a r s . This study has almost doubled the known, published records of shallow-water tanaidomorphan species in New Zealand and all of the species are likely to be r ecorded more widely than the records here imply